2009
DOI: 10.1038/cgt.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

Survivin knockdown by short hairpin RNA abrogates the growth of human hepatocellular carcinoma xenografts in nude mice

Abstract: Abnormal high activation of survivin is involved in carcinogenesis of various types of cancer. Survivin has been shown to promote cell proliferation in human hepatocellular carcinoma (HCC). Survivin-targeting approaches have become a promising strategy for treating HCC. Here, we used a reporter system to screen effective survivin siRNA sequences. The effect of vector-based survivin short hairpin RNA (shRNA) on the malignant phenotype of HCC cells in vitro and in vivo was determined, and an adenovirusmediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…Experimental data indicated that degradation of survivin was the main trigger for apoptosis induction. After the expression of survivin was downregulated, a marked block in the G 0 /G 1 phase of the cell cycle was observed and cell apoptosis induction was examined, which was similar to other reports that did not use this technique (32). These data have laid a foundation for further investigation into cervical carcinoma therapeutics.…”
supporting
confidence: 80%
“…Experimental data indicated that degradation of survivin was the main trigger for apoptosis induction. After the expression of survivin was downregulated, a marked block in the G 0 /G 1 phase of the cell cycle was observed and cell apoptosis induction was examined, which was similar to other reports that did not use this technique (32). These data have laid a foundation for further investigation into cervical carcinoma therapeutics.…”
supporting
confidence: 80%
“…Adding value to the clinical usefulness of oncofetal molecules, some of them have also been examined for their therapeutic potentials. Representative candidates include cadherin-17 and survivin, for which suppression of their levels is known as a way to counteract liver tumorigenesis in both in vitro and in vivo experimental settings (17,38). In this study, an alleviation of migration and invasion in HCC cells was clearly shown upon ASB4 suppression, providing a solid evidence for the involvement of ASB4 in the presentation of these tumor phenotypes.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, survivin knockdown caused radio-sensitization, which was paralleled by an increased activity of caspases, in wild type-p53 but not in mutant-p53 sarcoma cells [68], and in non-small cell lung cancer cell lines [69]. Recently, Zang et al [70] demonstrated that survivin knockdown, through the use of an adenovirus-mediated shRNA expression vector, inhibited the growth of human hepatocellular carcinoma cell lines, induced an apoptotic response and blocked the cell cycle in G 1 phase resulting in an apparent mitotic catastrophe. Furthermore, intratumoral injection of adenovirus-delivered survivin shRNA suppressed tumor growth inducing spontaneous apoptosis of cancer cells and significantly prolonging animal survival [70].…”
Section: Rnai-mediated Validation Of Survivin As a Therapeutic Targetmentioning
confidence: 99%
“…Recently, Zang et al [70] demonstrated that survivin knockdown, through the use of an adenovirus-mediated shRNA expression vector, inhibited the growth of human hepatocellular carcinoma cell lines, induced an apoptotic response and blocked the cell cycle in G 1 phase resulting in an apparent mitotic catastrophe. Furthermore, intratumoral injection of adenovirus-delivered survivin shRNA suppressed tumor growth inducing spontaneous apoptosis of cancer cells and significantly prolonging animal survival [70]. Finally, transfection of endothelial cells with survivin-specific siRNAs induced a marked increase in the rate of apoptosis, a dose-dependent inhibition of their migration on vitronectin, and a decrease in capillary formation [71].…”
Section: Rnai-mediated Validation Of Survivin As a Therapeutic Targetmentioning
confidence: 99%